2019
DOI: 10.11648/j.pbs.20190801.14
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dysfunctional Eating Attitudes and Parental Marital Status in Female Adolescents

Abstract: The purpose of this study is to investigate the relationship between dysfunctional eating attitudes and anorexic or bulimic symptoms with regard to the marital status of parents and also to investigate the difference in eating attitudes scores by means of body and weight satisfaction in adolescents. 60 adolescent girls attending high school participated in the study. Half of the involved participants consisted of families whose parents lived together, and the other half had divorced parents. The questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
1
Order By: Relevance
“…Other authors have established this relationship. Doksat et al in Turkey in 2017 had reported a relationship between adolescent girls at risk of eating disorders and parental marital status [30]. However, in contrast to the results of this work, the parents' divorced status was the one incriminated.…”
Section: Factors Associated With Eating Disorders In Multivariate Ana...contrasting
confidence: 83%
“…Other authors have established this relationship. Doksat et al in Turkey in 2017 had reported a relationship between adolescent girls at risk of eating disorders and parental marital status [30]. However, in contrast to the results of this work, the parents' divorced status was the one incriminated.…”
Section: Factors Associated With Eating Disorders In Multivariate Ana...contrasting
confidence: 83%